Staphylococcus aureus adaptation to the host and persistence: Role of loss of capsular polysaccharide expression - Tuchscherr, Lorena Paola Nelly (2010)
A vast array of virulence factors enable Staphylococcus aureus to readily adapt to different environmental niches in diverse hosts. The cap gene cluster is present in almost all relevant clinical S. aureus isolates and capsular polysaccharide expression is apparent in isolates from patients with acute infection. The number of S. aureus isolates from patients with chronic infections that do not express capsular polysaccharide, however, is significantly high, indicating that loss of capsular polysaccharide expression may be a key S. aureus feature associated with persistence. The role of the loss of capsular polysaccharide expression as well as the emergence of other defined phenotypes and their relevance to persistence of S. aureus and chronicity of the infection is discussed in this article. © 2010 Future Medicine Ltd.